Karakteristik Budaya Organisasi Unggul Berbasis Kearifan Lokal di Industri Batik Masaran Sragen Jateng - Hakim, Lukman; Sugiyanto, Eko (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2020)
This study aims to: (1) identify the characteristics of superior organizational cultures in the Masaran Sragen Batik Industry in Central Java. (2) identifying the role of superior organizational culture in the Central Java Masaran Batik Industry. (3) analyzing the values that underlie the existence of superior organizational culture in the Masaran Batik Industry of Sragen, Central Java. The study used a qualitative descriptive method with a case study approach. Case study data were obtained from interviews, observations, and documentation or archives. To get data that is truly valid, then the validity of the data checking uses a triangulation technique that is checking or as a comparison of the data. The results of the study can be concluded that the characteristics of superior organizational culture in the Laweyan batik industry, as follows: (1) the nature of transparency, (2) There is the nature of accuracy (detaility) (3) There is a dynamic nature in managing the industry (4) There is a Proactive nature in addressing an ever changing environment. (5) The nature of Professionalism, (6) The existence of mutual cooperation, (7) There is a creative nature in managing the company.